Bacterial Butyrate in Parkinson's Disease Is Linked to Epigenetic Changes and Depressive Symptoms - Xie, Aoji; Ensink, Elizabeth; Li, Peipei; Gordevičius, Juozas; Marshall, Lee L.; George, Sonia; Pospisilik, John Andrew; Aho, Velma T.E.; Houser, Madelyn C.; Pereira, Pedro A.B.; Rudi, Knut; Paulin, Lars; et al. (Movement disorders, 2022)
Background The gut microbiome and its metabolites can impact brain health and are altered in Parkinson's disease (PD) patients. It has been recently demonstrated that PD patients have reduced fecal levels of the potent epigenetic modulator butyrate and its bacterial producers. Objectives Here, we investigate whether the changes in the gut microbiome and associated metabolites are related to PD symptoms and epigenetic markers in leucocytes and neurons. Methods Stool, whole blood samples, and clinical data were collected from 55 PD patients and 55 controls. We performed DNA methylation analysis on whole blood samples and analyzed the results in relation to fecal short‐chain fatty acid concentrations and microbiota composition. In another cohort, prefrontal cortex neurons were isolated from control and PD brains. We identified genome‐wide DNA methylation by targeted bisulfite sequencing. Results We show that lower fecal butyrate and reduced counts of genera Roseburia, Romboutsia, and Prevotella are related to depressive symptoms in PD patients. Genes containing butyrate‐associated methylation sites include PD risk genes and significantly overlap with sites epigenetically altered in PD blood leucocytes, predominantly neutrophils, and in brain neurons, relative to controls. Moreover, butyrate‐associated methylated‐DNA regions in PD overlap with those altered in gastrointestinal (GI), autoimmune, and psychiatric diseases. Conclusions Decreased levels of bacterially produced butyrate are related to epigenetic changes in leucocytes and neurons from PD patients and to the severity of their depressive symptoms. PD shares common butyrate‐dependent epigenetic changes with certain GI and psychiatric disorders, which could be relevant for their epidemiological relation. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society